2021
DOI: 10.1016/j.jdent.2020.103534
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of N95 respirators against SARS-CoV-2: A scoping review

Abstract: Objectives This scoping review aimed to map and compile the available evidence regarding the effectiveness of decontaminating N95 respirators against the novel coronavirus (SARS-CoV-2). Data We selected studies written in English assessing or discussing the decontamination strategies of N95 respirators against SARS-CoV-2. Two independent researchers performed the search and study screening. A descriptive analysis was carried out considering the study design of the inclu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 88 publications
0
23
0
1
Order By: Relevance
“…The targeted allocation of appropriate PPE is therefore of paramount importance for dental healthcare providers. Reuse of respirators may alleviate the problem of PPE scarcity, but further research into safe and cost-effective decontamination procedures is required [23].…”
Section: Domainmentioning
confidence: 99%
“…The targeted allocation of appropriate PPE is therefore of paramount importance for dental healthcare providers. Reuse of respirators may alleviate the problem of PPE scarcity, but further research into safe and cost-effective decontamination procedures is required [23].…”
Section: Domainmentioning
confidence: 99%
“…One-hour treatment in a climate chamber at 70 °C with 75% humidity rate was shown to be adequate for enabling substantial decontamination of FFP2s [ 7 ]. Recent literature reviews concluded that the evidence supporting appropriate decontamination strategies for FFP2 respirators remains scarce, although ultraviolet irradiation and vaporized hydrogen peroxide seem to be the current recommended standard [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several meta-analyses that compare the performance of various mask decontamination methods. [ 106 , 118 , [144] , [145] , [146] , [147] ] Although a certain degree of inconsistency exists, it appears that most meta-analyses have drawn the conclusion that VHP is the most reliable and safest method to decontaminate N95 masks for multiple cycles.…”
Section: Decontamination and Reuse Of Masksmentioning
confidence: 99%